Transformations in the discipline of geography experienced over 60 years by a Norwegian geographer. Issue 4 (8th August 2019) - Holt-Jensen, Arild
ABSTRACT: The article presents the changes in the discipline of geography over 60 years as experienced both in fieldwork and in practice by a Norwegian geographer. Based on diaries and collections of memoirs, the author, Arild Holt-Jensen, presents his life story and how it has been impacted by people, places and special events. His intention is to show how geography and his own work reflect social, political and intellectual changes since the late 1950s. Initially, a regional geography approach was adopted in the fieldwork for his master's thesis but the approach was challenged by new ideas and methods from both the spatial science school and model thinking. As a young lecturer in 1968, the author was shocked by the positivism debate and critical philosophy, and his spatial science and quantitative approach in his PhD project had to be adapted. His political engagement and interest in planning led him to research social exclusion in European neighbourhoods. His need to trace the identity of geography as a discipline resulted in a textbook that throughout the years has been updated by following up on research trends to the present. Thus, the book and the article show Holt-Jensen's shifts in disciplinary identity and research practice.